{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# chapter7 - Chapter 7 Solutions to §7.1 1(Lf(x =(D – x(2x...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 7 Solutions to §7.1 1. (Lf)(x) = (D – x)(2x – 3e 2x ) = D(2x – 3e 2x ) – x(2x – 3e 2x ) = (2 – 6e 2x ) – 2x 2 + 3xe 2x = 2(1 – x 2 ) + 3e 2x (x – 2). 3. (Lf)(x) = (D 3 – 2xD 2 )(2x – 3e 2x ) = D 3 (2x – 3e 2x ) – 2xD 2 (2x – 3e 2x ) = D 2 (2 – 6e 2x ) – 2xD(2 – 6e 2x ) = D(–12e 2x ) – 2x(–12e 2x ) = –24e 2x + 24xe 2x = 24e 2x [x – 1]. 5. Lf = (D 2 – x –1 D + 4x 2 )(sin(x 2 )) = D 2 (sin(x 2 )) – x –1 D(sin(x 2 )) + 4x 2 (sin(x 2 )) = D(2xcos(x 2 )) – x –1 (2xcos(x 2 )) + 4x 2 (sin(x 2 )) = 2[cos(x 2 ) – 2x 2 sin(x 2 )] – 2cos(x 2 ) + 4x 2 (sin(x 2 )) = 0. Thus, f ∈ Ker(L). 7. (L 1 L 2 )f = L 1 (f´ – 2x 2 f) = (xD + 1)(f´ – 2x 2 f) = xf´´ – 2x 3 f´ – 4x 2 f + f´ – 2x 2 f = xf´´ + (1 – 2x 3 )f´ – 6x 2 f, so that L 1 L 2 = xD 2 + (1 – 2x 3 )D – 6x 2 . (L 2 L 1 )f = L 2 (xD + 1)f = (D – 2x 2 )(xf´ + f) = xf´´ + f´ + f´ – 2x 2 (xf´ + f) = xf´´ + 2(1 – x 3 )f´ – 2x 2 f. Thus, L 2 L 1 = xD 2 + 2(1 – x 3 )D – 2x 2 , so that L 1 L 2 ≠ L 2 L 1 . 9. (L 1 L 2 ) = L 1 (D + b 1 )f = (D + a 1 )(f´ + b 1 f) = f´´ + [b 1 + a 1 ]f´ + (b 1 ´ + a 1 b 1 )f. Thus L 1 L 2 = D 2 + (b 1 + a 1 )D + (b 1 ´ + a 1 b 1 ). Similarly, L 2 L 1 = D 2 + (a 1 + b 1 )D + (a 1 ´ + b 1 a 1 ). Thus L 1 L 2 – L 2 L 1 = (b 1 ´ – a 1 ´), which is the zero operator if and only if b 1 ´ = a 1 ´. which can be integrated directly to obtain b 1 = a 1 + c 2 , where c 2 is an arbitrary constant. Consequently we must have: L 1 = D + a 1 (x), L 2 = D + [a 1 (x) + c 2 ]. 11. (D 2 + 4xD – 6x 2 )y = x 2 sin x and y´´ + 4xy´ – 6x 2 y = 0. 209 210 Ch. 7 Linear Differential Equations of Order n 13. Let a 1 , ..., a n be functions that are continuous on an interval I. Then, for any x in I, the initial value problem y (n) + a 1 (x)y (n – 1) + ... + a n – 1 (x)y´ + a n (x)y = 0, y(x ) = 0, y´(x ) = 0, ..., y (n – 1) (x ) = 0, has only the trivial solution y(x) = 0. Proof All of the conditions of the existence–uniqueness theorem are satisfied and y(x) = 0 is a solution; consequently, it is the only solution. 15. Substituting y(x) = e rx into the given DE yields e rx (r 3 + 3r 2 – 4r – 12) = 0, so that we will have a solution providing r satisfies r 3 + 3r 2 – 4r – 12 = 0, that is, (r – 2)(r + 2)(r + 3) = 0. Consequently, three solutions to the given DE are y 1 (x) = e 2x , y 2 (x) = e –2x , y 3 (x) = e –3x . Further, the Wronskian of these solutions is W[y 1 , y 2 , y 3 ](x) = e 2x e –2x e –3x 2e 2x –2e –2x –3e –3x 4e 2x 4e –2x 9e –3x = –20e –3x . Since the Wronskian is never zero, the solutions are LI on any interval. Hence the general solution to the DE is y(x) = c 1 e 2x + c 2 e –2x + c 3 e –3x ....
View Full Document

{[ snackBarMessage ]}

### Page1 / 10

chapter7 - Chapter 7 Solutions to §7.1 1(Lf(x =(D – x(2x...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online